Pelatihan Pembuatan Artikel Ilmiah bagi Mahasiswa Prodi PPKn Universitas Muhammadiyah Ponorogo - Ambiro Puji Asmaroini; Hadi Cahyono (J-ABDIPAMAS (Jurnal Pengabdian Kepada Masyarakat), 2018)
Academic articles means as the development of student knowledge. Some benefits can be obtained from writing the academic articles. The benefits of writing the academic articles are: 1) delivering and developing ideas from students, 2) giving the academic impact for the students, 3) having a scientific work in the form of academic articles that can be published at local, national, and international journals. Training for writing the academic articles for the civic education students, Muhammadiyah University of Ponorogo aimed to make students understand how to create academic articles and able to determine the ideas tha have to be written in making academic articles. The methods used in this activity include training and practice, interviews / interviews, and lectures. There were 32 students of Civic education students who attend the training and they produced 15 titles of academic articles. The title was developed into an academic article framework. In the last stage, one of the selected student articles was published in the journal of Education and Citizenship Program of Civic Education Department, Muhammadiyah University of Ponorogo, January 2018 edition.Keywords: academic articles, students of Civic Education, Journal articleABSTRAKArtikel ilmiah merupakan sarana mengembangkan pengetahuan mahasiswa. Banyak manfaat yang bisa diperoleh dari penulisan artikel ilmiah. Adapun manfaat yang diperoleh menulis artikel ilmiah antara lain: 1) Menyampaikan dan mengembangkan ide dari mahasiswa, 2) memberikan dampak yang akademis bagi mahasiswa, 3) Memiliki karya berupa artikel ilmiah yang bisa dipublikasikan melalui jurnal lokal, nasional, maupun internasional. Pelatihan pembuatan artikel ilmiah bagi mahasiswa prodi PPKn Universitas Muhammadiyah Ponorogo bertujuan agar mahasiswa memahami cara dalam membuat artikel ilmiah dan mampu menemukan ide yang akan dituliskan dalam membuat artikel ilmiah. Adapun metode yang digunakan dalam kegiatan ini adalah meliputi pelatihan dan praktik, tanya jawab / interview, dan ceramah. Dari sekian mahasiswa prodi PPKn Universitas Muhammdiyah Ponorogo, terdapat 32 Mahasiswa yang mengikuti pelatihan, menghasilkan 15 judul artikel ilmiah. Judul tersebut dikembangkan menjadi artikel ilmiah. Pada akhirnya, salah satu artikel karya mahasiswa terpilih, berhasil diterbitkan di jurnal Pendidikan dan Kewarganegaraan Prodi PPKn Universitas Muhammadiyah Ponorogo edisi Januari 2018.